2001
DOI: 10.1007/s001980170158
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density and Quantitative Ultrasound Parameters in Patients with Klinefelter's Syndrome after Long-Term Testosterone Substitution

Abstract: Klinefelter's syndrome (KS) is a common sex chromosomal disorder associated with androgen deficiency and osteoporosis. Only few bone mineral density (BMD) and no quantitative ultrasound (QUS) data are available in these patients after long-term testosterone replacement therapy. We examined in a cross-sectional study 52 chromatin-positive KS patients aged 39.1 +/- 12.4 years (mean +/- SD). Patients had been treated with oral or parenteral androgens for 9.2 +/- 8.2 years (range 1-32 years). Areal BMD and bone mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 51 publications
3
47
0
1
Order By: Relevance
“…1993). In some studies involving subjects with genetic disorders performed by densitometric measurements (Kao et al 1992;Sepulveda 1995;Angelopoulou et al 1999;Angelopoulou et al 2000;van der Bergh et al 2001;Sakamidis at al. 2002;Baptista et al 2004), significant differences in comparison with controls were usually shown.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…1993). In some studies involving subjects with genetic disorders performed by densitometric measurements (Kao et al 1992;Sepulveda 1995;Angelopoulou et al 1999;Angelopoulou et al 2000;van der Bergh et al 2001;Sakamidis at al. 2002;Baptista et al 2004), significant differences in comparison with controls were usually shown.…”
Section: Introductionmentioning
confidence: 98%
“…In cross-sectional studies (Lippuner et al 2000;Wüster et al 2001;Drozdzowska 2003), this method proved an ability to discriminate between healthy people and individuals with different types of low-trauma fractures. Recently, in some studies, QUS measurements were used to establish skeletal status in subjects with genetic disorders (Aspray et al 1998;van der Bergh 2001;Pluskiewicz et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This observation together with reports that delayed testosterone therapy in men with Klinefelter syndrome diminishes the gain in BMD may indicate that the adolescents with delayed puberty, IHH, Kallmann syndrome and Klinefelter syndrome may benefit from early assessment of BMD and early treatment of hypogonadism to achieve expected peak bone mineral density [81,82].…”
Section: Androgensmentioning
confidence: 78%
“…The pharmacokinetic limitations of the available injectable testosterone esters dictate that stable blood testosterone concentrations in the physiological range are achieved with injections at the rate of 100 mg per week, ideally with actual 100 mg injections each week (34,44,45). In practice, however, many patients do not accept regular weekly injections and this regimen is often relaxed to 200 mg every 2 weeks, although such regimens still often encounter significant non-adherence to a regular schedule (15). Maintaining the same weekly dosing at longer (3 or more weeks) inter-injection intervals leads to increasingly extreme fluctuations in blood testosterone levels and, consequentially, in mood and behavioural swings.…”
Section: Discussionmentioning
confidence: 99%